The Stock Market and Cooperatives - Jiménez Méndez, Edgar Ricardo (Cooperativismo & Desarrollo, 2014)
It is now apparent that the stock market, as it has continued to develop in Colombia, offers access to a greater number of participants. Accordingly, cooperative societies and medium-sized enterprises have more opportunities. This document presents one of the options for accessing the primary market in Colombia. In this sense, the alternative stock market becomes an effective tool that has demonstrated results in Europe, and given the similarity to a great number of Colombian companies, it is an option that is worth keeping in mind. This study shows how alternative stock markets function in industrialized countries such as Spain, England and France, in order to draw a parallel with Colombia, and stimulate debate around the possibility of consolidating a similar model in Colombia.